Apostrofy do wód – nowe spojrzenie na cykl epigramów w czwartej księdze Marcjalisa (18; 22 i 63) - Pieczonka, Joanna (Collectanea Philologica, 2018)
The article focuses on the Martial’s poems no. 18, 22 and 63 from the Book 4 of epigrams. These poems unite in a cycle of epigrams with a common motif of an apostrophe to water appearing in the last line of each epigram. Although this cycle has been previously disputed in an article by Mark A. P. Greenwood (‘Talking to Water’: An Epigram-Cycle in Martial, Book 4 (4.18; 4.22; 4.63), RhM 141 (1998), 367–372), the author finds it necessary to reassess the epigrams. As a result of these analyses the author discovers the links and the differences between the poems that have not been noted before. Furthermore the article presents the possible connections between the cycles and suggests that they form a complex structure, a whole web, inside the Book 4. Concluding, the author puts forward a hypothesis that perhaps this special arrangement of epigrams (complied with the principle of cohesion and variety) exceeds the boundaries of Book 4.